COMMUNITY DEVELOPMENT UMKM EKS LOKALISASI DOLLY MELALUI DIGITAL PLATFORM DALAM MENGHADAPI COVID-19 - Putu Aditya Ferdian (Universitas Airlangga, 2021)
The closure of Dolly's localization in 2014 had a significant impact on the economy of the surrounding community. Where Dolly is known as the largest prostitution place in Southeast Asia, which is in Putat Jaya, Sawahan District, City of Surabaya. The solution that has been carried out by the Surabaya City Government is to provide training for MSMEs (Micro, Small and Medium Enterprises), in order to create economic growth and opportunities for new creative businesses in local society. To strengthen the MSMEs sector that has been initiated by the Surabaya City Government, our team wants to provide an added value to these MSMEs by carrying out capacity building and a touch of digital platforms to develop the community business sector. So, existing MSME products can be promoted according to the correct and appropriate techniques. This aims to create a creative economy that can be independent from localization activities and can survive the Covid-19 pandemic.